Back Cover: Comprehending Metal Particle Combustion: a Path Forward (Prop., Explos., Pyrotech. 7/2022). Issue 7 (13th July 2022) - Altman, Igor; Pantoya, Michelle
Abstract : The cover image is based on the Research Article Comprehending Metal Particle Combustion: a Path Forward by Igor Altman and Michelle Pantoya https://doi.org/10.1002/prep.202200040